The use of industry 4.0 tools in the implementation of skills management: a bibliometric analysis on the impacts in the process - Barollo, Bruna Vieira; Rodrigo (Brazilian Journal of Production Engineering, 2022)
Recently, the fourth industrial revolution has introduced new innovative technologies that enable higher quality and cost reduction, but it has generated an intensification of market demands, increasing business complexity and reinforcing the need to develop new skills and competences. Therefore, the present study aims to understand the main difficulties encountered by companies in the process of implementing Management by Competencies, and which Industry 4.0 tools are being studied and applied in the HR sector, so that it is possible to identify the solutions with the greatest potential. to simplify and operationalize this model of strategic people management. For this, the 1st phase of the research applies the method of bibliometric analysis seeking articles related to the implementation of Management by Competencies; and in the 2nd phase, bibliometric analysis is applied focused on retrieving scientific productions related to people management in I4.0. Finally, this study allowed us to map resources, tools and strategies identified as viable and efficient solutions to mitigate the barriers commonly faced by companies in Competency Management, enabling a form of management that places the human factor at the center of the strategy.
Keywords: Management by Competencies; Industry 4.0; people management; managerial model